Enhanced sensitivity in THz plasmonic sensors with silver nanowires. Issue 1 (December 2018) - Hong, J.; Jun, S.; Cha, S.; Park, J.; Lee, S.; Shin, G.; Ahn, Y.
Abstract We developed hybrid slot antenna structures for microbial sensing in the THz frequency range, where silver nanowires (AgNWs) were employed to increase the sensitivity. In order to fabricate the hybrid devices, we partially etched the AgNW in the slot antenna region, where we can expect the field enhancement effect at the AgNW tip. We measured the resonant-frequency shift observed upon the deposition of a polymer layer, and observed that the sensitivity increased upon the introduction of AgNWs, with an enhancement factor of more than four times (approximately six times in terms of figure-of-merit). The sensitivity increased with the AgNW density until saturation. In addition, we tested devices with PRD1 viruses, and obtained an enhancement factor of 3.4 for a slot antenna width of 3 μm. Furthermore, we performed finite-difference time-domain simulations, which confirmed the experimental results. The sensitivity enhancement factor decreased with the decrease of the slot width, consistent with the experimental findings. Two-dimensional mapping of the electric field confirmed the strong field localization and enhancement at the AgNW tips.